O discurso de pessoas privadas de liberdade com a tuberculose à luz da história oral de vida - Alves, Rayanne Santos (2012)
The access of the population carcerária to the actions and services of health is defined by the National Plan of Health in the System Prisoner, who emphasizes the guarantee of the right to the health for the set of the Brazilian population. In this, there are included the Deprived Persons of Freedom, bordered in prison establishments, which makes the minimização of the differences between the life intrawalls and to extrawalls basically for the reduction of the iniquities and the universalização of the access to the health. So, the plan is an instrument for inclusion of the detainees in the System Only one of Health. Prisoners constitute the tuberculosis and the prisons like serious problems of public health and the actions of the control of this disease in the spaces it has when if deficients were shown. The study aimed to analyse the actions of control of the tuberculosis turned to the private persons of freedom, according to the determinations of the National Plan of Health in the System Prisoner of the unities masculine prisons of the local authority of John Pessoa, State of Paraíba. It the question is a study avaliativo qualitative nature. The subjects of the inquiry are seven private persons of freedom of the masculine sex with history of adoecimento for tuberculosis, notified in the year of 2011. For construction of the empirical material there was used the technique of the oral history and for reading of the obtained informations, when analysis of the speech was done. Referent to the actions of control of the tuberculosis in the extent prisoner, the subjects pointed, in his speeches, to lack of preventive measures of the disease, reporting, for times, insalubridades of the enclosures (cells), the food inapropriada to a patient of tuberculosis and negligence for part of the agents prisoners for with the mobilization of transporting them to the service of health. According to speeches uttered by such collaborators, the care in the control of the tuberculosis is carried out, predominantly, in situations that the disease was already installed in the individual and the directions of the professionals of health consist in the maintenance of the healthy condition of same after or during the persistence of debilidades biological produced by the clinical picture of adoecimento for tuberculosis, advising for continuity of the regular ingesta and daily rate of the bacteriostáticos and direction prescritiva for I it do not use drugs. The narratives point to ineffective knowledge on the forms of infection of the disease, link the attack for tuberculosis to the tobaccoism and use of illicit drugs; they make speeches made a list to the stigma of the tuberculosis in the relations with the too much punished ones, which it shows fragilidades of informations on the disease for part of the punished ones. The discursive fragments surface negative senses of is ill of tuberculosis in the prison. In order to surpass the difficulties as for the access to the health of the punished ones and to the efficient control of the tuberculosis between this population, one needs the undertaking of efforts, for part of the State, of the management of the prison and of the professionals of health, in the execution of actions in health cohesive with the politics of health turned to this population and efetivação the Laws of Penal Executions. Such measures collaborate in destroying the iniquities inherent in the beginning of the universalização of the access to the health indistinct of the Brazilian population.